1998
DOI: 10.1086/316211
|View full text |Cite
|
Sign up to set email alerts
|

A Long‐Period Spectroscopic Binary in the O‐Star Multiple System HD 193322

Abstract: We present radial velocity measurements and a single-lined spectroscopic orbit for the bright Otype star, HD 193322A, which we show to be a 311 day binary system that has a distant third companion (detected by speckle interferometry) in a 31 yr orbit. We suggest that the speckle companion appears in the spectrum as a broad-lined component of early B type. We also present a spectrum of the visual companion, HD 193322B, which appears to be an unresolved, double-lined spectroscopic binary. Thus, HD 193322, the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Nevertheless, the spectral properties of the components are sufficiently different in this case that we may attempt radial velocity measurements. The appearance of the optical spectrum is dominated by a narrow-lined component that corresponds to the primary star in the close orbit, Ab1 (McKibben et al 1998). The secondary in the close orbit, Ab2, is fainter and contributes little to the composite spectrum ( §5).…”
Section: Radial Velocities Of Ab1mentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the spectral properties of the components are sufficiently different in this case that we may attempt radial velocity measurements. The appearance of the optical spectrum is dominated by a narrow-lined component that corresponds to the primary star in the close orbit, Ab1 (McKibben et al 1998). The secondary in the close orbit, Ab2, is fainter and contributes little to the composite spectrum ( §5).…”
Section: Radial Velocities Of Ab1mentioning
confidence: 99%
“…The results are presented in Table 5 that lists the heliocentric Julian date of midexposure, the corresponding orbital phases in the close and wide systems (see below), the measured radial velocity and its associated error, a correction term for line blending effects, the observed minus calculated velocity residual from the fit (see below), and the observation source number from Table 4. Note that for completeness we have included in Table 5 velocities published earlier by McKibben et al (1998; indicated by a 0 in the final column).…”
Section: Radial Velocities Of Ab1mentioning
confidence: 99%
See 2 more Smart Citations
“…The preliminary 31 y orbit (Hartkopf et al 1993) had very small residuals but under sampled phase space (covering only 9% of the orbit). Subsequent to this, the A component was recognized as a close 311 d spectroscopic binary (McKibben et al 1998). In addition to the speckle resolution listed in Table 2, separated fringe packet solutions with the CHARA Array have been obtained several times since 2005.…”
Section: Notes On Stars Listed Inmentioning
confidence: 99%